Review of Sicakra Digital Archive Management at the Admin Finance Division of PT. Cakra Putra Parahyangan Tasikmalaya - Ananda, Silvina; Eko Setyasari, Untung; Kurniadi, Yudi (Lafadz Jaya Publisher, 2024)
The purpose of this research is to find out the management of Sicakra's digital archives which includes digital archive management facilities and to find out the positive impact of digital archive management for the company. This research uses a qualitative descriptive approach by describing and analyzing problems related to digital archive management. Primary and secondary data form the basis of qualitative research. The primary data of this research was obtained through documentation, observation, and interviews, while secondary data was obtained from books, research and related articles. From the results of this study, it is known that PT. Cakra Putra Parahyangan Tasikmalaya is still in the process of implementing digital archive management. The initial step taken is to carry out manual archive management habits and then input them into the digital archive, Sicakra. There are still many obstacles in the implementation process, one of which is the factor of human resources who are still reluctant to work double in archiving. Nevertheless, the company will still make a gradual transition from manual to digital archive management, through Sicakra. The background to this change is that there are more benefits when the company implements Sicakra, starting to facilitate and speed up the process of sending, sharing and searching, saving physical storage space, as well as providing more efficient access. Thus, this research shows that digital archive management can benefit companies, such as improving operational efficiency and resource management.